Emerging doctor of pharmacy program in India: A survey on general opinion of selected educated Indians - Raman Garipelly; Shilpa Garg; Uday Venkat Mateti (Wolters Kluwer Medknow Publications, 2012)
Objective: The aim of this study was to evaluate the awareness and perception of general educated Indian individuals about Doctor of Pharmacy course. Methods: A cross-sectional structured Pharm.D questionnaire survey was conducted at educational institutions of India mainly through e-mails. Pharm.D questionnaire survey was conducted over a period of six months. The questionnaire was classified into four major categories, including course-related questions, roles-related questions, critical comparative questions, and opinion-based questions. The responses were collected and analyzed to assess the opinions and attitudes of the study population regarding the course Pharm.D. Findings: Out of 2819 responses, 66.01% agreed that Indian syllabus, teaching procedure, and hospital training in institutions are enough to prepare an ideally graduated Pharm.D. Respondents of about 70.59% agreed that Pharm.Ds should take care of complete responsibility of drug therapy rather than physicians prescribing the medications and Pharm.Ds fixing the dose. The statement "Pharm.Ds play a vital role in improving medication adherence through patient counseling" was accepted by 47.80%, whereas 41.40% did not accept it as they felt that the Pharm.D's role in this regard is not more than the physician's role, and 10.80% suggested that other healthcare professionals would play a better role. Among all the respondents, 73.64% of the study population was found to be ready for giving equal credit and respect to Pharm.Ds as physicians. Conclusion: Our survey emphasizes on the opinion of educated people of having Pharm.Ds in both government and private hospitals to take care of complete therapy and for improving medication adherence.